2016
DOI: 10.5334/jbr-btr.974
|View full text |Cite
|
Sign up to set email alerts
|

Non-Puerperal Uterine Inversion

Abstract: We report a case of non-puerperal uterine inversion, illustrating the correlation between MRI and pre-operation macroscopic images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The non-puerperal type is mainly associated with uterine tumours located at the uterine fundus, which force the fundus to invert into the uterine cavity. It has been reported that the majority of the cases in the literature were associated with benign tumours of the uterus, mainly leiomyomas [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The non-puerperal type is mainly associated with uterine tumours located at the uterine fundus, which force the fundus to invert into the uterine cavity. It has been reported that the majority of the cases in the literature were associated with benign tumours of the uterus, mainly leiomyomas [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Uterine inversion can be divided into two major types: puerperal and nonpuerperal, with the latter accounting for 17% of all uterine inversion cases. 1 The average age of patients with uterine inversion is 46.3 years, and affected patients often complain of abdominal pain and irregular bleeding. 2 The majority of cases are caused by uterine myoma, with rare cases due to malignant uterine cancer or sarcoma.…”
Section: Introductionmentioning
confidence: 99%
“… 2 The majority of cases are caused by uterine myoma, with rare cases due to malignant uterine cancer or sarcoma. 1 , 2 Meanwhile, the characteristic magnetic resonance imaging (MRI) findings are a V‐shaped depressed uterine fundus and a tumor showing a bull's‐eye sign in the vaginal cavity. 3 Uterine repositioning on nonpuerperal uterine inversion has risks of uterine perforation and heavy bleeding resulting in severe blood loss.…”
Section: Introductionmentioning
confidence: 99%